2017
DOI: 10.1103/physreve.95.032905
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental structural characteristics of planar granular assemblies: Self-organization and scaling away friction and initial state

Abstract: The microstructural organization of a granular system is the most important determinant of its macroscopic behavior. Here we identify the fundamental factors that determine the statistics of such microstructures, using numerical experiments to gain a general understanding. The experiments consist of preparing and compacting isotropically two-dimensional granular assemblies of polydisperse frictional disks and analyzing the emergent statistical properties of quadrons-the basic structural elements of granular so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Such time dependence is expected because the contact event rate is likely to be sensitive to the intergranular force distribution, which is position-and time-dependent. Indeed, it has been argued [10,19] that the structural evolution of a granular system is a self-organisation process coupled to the evolution of the intergranular forces. Therefore, these equations and their extension form an important step towards a complete understanding of the structure-forces co-evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such time dependence is expected because the contact event rate is likely to be sensitive to the intergranular force distribution, which is position-and time-dependent. Indeed, it has been argued [10,19] that the structural evolution of a granular system is a self-organisation process coupled to the evolution of the intergranular forces. Therefore, these equations and their extension form an important step towards a complete understanding of the structure-forces co-evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that clapping is a genuine phenomenon and study the effect of the driving on it, we analysed a long-time DEM simulation of a bi-axial compression. The simulated system consisted of 22,381 discs, whose diameters were distributed log-normally [9,10]. The disc interaction was harmonic, with tangential and normal spring constants k t and k n , respectively, obeying k t ∕k n = 1∕4 .…”
Section: Bi-axial Compression Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…With this definition, the total volume of the system is a sum of all the cell volumes, . This definition differs from that in Matsushima and Blumenfeld [10,11], where a cell is defined by the shortest (irreducible) closed loop of contact points around a void. Nevertheless, this difference is of no major consequence in disc systems.…”
Section: Cell Structure and Cell Stressmentioning
confidence: 97%
“…Nicot and Darve [9] proposed a constitutive model, focusing on 6-cell structures. Matsushima and Blumenfeld [10,11] studied the structural properties of cells in details and showed that the cell shape is elongated the most when the cell order is around six, because elongated cells of higher cell order are less stable mechanically. Recently, Wanjura et al [12] developed a model for cell structure evolution, based on the statistics of cell making and breaking during quasi-static dynamics.…”
Section: Introductionmentioning
confidence: 99%